2005
DOI: 10.1002/app.21327
|View full text |Cite
|
Sign up to set email alerts
|

Using silica nanoparticles as curing reagents for epoxy resins to form epoxy–silica nanocomposites

Abstract: Nanoscale colloidal silica showed high reactivity toward curing epoxy resins to form epoxy-silica nanocomposites under mild conditions. Adding a certain amount (5000 ppm) of magnesium chloride lowered the activation energy of the reaction from 71 to 46 kJ/mol. Less and more magnesium chloride both exhibited counter action on lowering the activation energy of the curing reaction. Tin chloride dihydrate and zinc acetylacetonate hydrate were also added into the curing compositions, however, showing no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…A comparison of values for both systems shows a decrease in Tp for nanocomposite of VE671 + 4% SN system. The exothermic heat of the samples containing SN is lower than that of the samples without SN and this result is in a good agreement with the previous reports [6,10]. Therefore, we can save energy and time in nanocomposite.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…A comparison of values for both systems shows a decrease in Tp for nanocomposite of VE671 + 4% SN system. The exothermic heat of the samples containing SN is lower than that of the samples without SN and this result is in a good agreement with the previous reports [6,10]. Therefore, we can save energy and time in nanocomposite.…”
supporting
confidence: 94%
“…[5,8] Epoxy-silica nanocomposites can be used in adhesives, coatings, packaging materials for electronic devices, matrices of advanced composites with improved performance, and many other fields. [6,9,10] Liu et al have reported that nanoscale colloidal silica particles act as a curing agent in the curing state of epoxy-silica nanocomposite formation. It was showed an interesting reactivity of silica nanoparticles (SN) toward epoxy resins without the need of adding other catalyst in cure reaction.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, aggregation of the inorganic nanomaterials is still commonly encountered even using the organo-modified inorganic nano-additives. Although in some reported cases the polymer nanocomposite materials could possess very high contents of inorganic nanomaterials [11], the amount of inorganic nanomaterials loaded to polymer matrixes is usually strictly limited.…”
Section: Introductionmentioning
confidence: 99%
“…Ragosta et al [11] 4 detected a reaction between the epoxy groups and silanol groups present on the surface of silica nanoparticles, leading to increased interfacial adhesion. Dispersed silica nanoparticles have been used as a curing agent in an epoxy system in the presence of magnesium chloride, acting as a catalyst, to yield a silica-epoxy nanocomposite [20]. Incorporation of silica nanoparticles and silicates has been reported to raise the glass transition temperature, T g , of the resulting nanocomposite (cyanate ester composites [9], vinyl ester composites [1], epoxy composites [13,21]) but also to reduce Tg (clay-biobased epoxy nanocomposites [18]).…”
Section: Introductionmentioning
confidence: 99%